Transformasi Manajemen Pemasaran Di Era Digital: Pendekatan Strategis Berbasis Teknologi Dan Perilaku Konsumen Modern - Sari, Vina Winda; Simatupang, Bahagia; Zen, Husnul (Digital Business Progress, 2025)
The development of digital technology has significantly transformed the marketing landscape, compelling companies to adopt more adaptive, interactive, and data-driven marketing management strategies. This article discusses the transformation of marketing management in the digital era through literature analysis, identification of digital strategy methods, and evaluation of their implementation effectiveness based on a conceptual study. The results indicate that digital marketing enhances communication efficiency, service personalization, and the effectiveness of customer acquisition strategies. However, challenges such as algorithm changes, data security, and intense digital competition require continuous innovation. This article provides practical implications for organizations to improve competitiveness through integrated digital marketing management.